Multiregional sequencing and circulating tumour DNA analysis provide complementary approaches for comprehensive disease profiling of small lymphocytic lymphoma. (22nd July 2021) - Moia, Riccardo; Favini, Chiara; Ferri, Valentina; Forestieri, Gabriela; Terzi Di Bergamo, Lodovico; Schipani, Mattia; Sagiraju, Sruthi; Andorno, Annalisa; Rasi, Silvia; Adhinaveni, Ramesh; Talotta, Donatella; Al Essa, Wael; et al.
Summary: We aimed at molecularly dissecting the anatomical heterogeneity of small lymphocytic lymphoma (SLL), by analysing a cohort of 12 patients for whom paired DNA from a lymph node biopsy and circulating cells, as well as plasma‐circulating tumour DNA (ctDNA) was available. Notably, the analyses of the lymph node biopsy and of circulating cells complement each other since a fraction of mutations (20·4% and 36·4%, respectively) are unique to each compartment. Plasma ctDNA identified two additional unique mutations. Consistently, the different synchronous sources of tumour DNA complement each other in informing on driver gene mutations in SLL harbouring potential prognostic and/or predictive value.